Competition between evaporation and fragmentation in nuclear reactions at 15-20 AMeV beam energy - Morelli, Luca <1982> (Alma Mater Studiorum - Università di Bologna, 2011)
The reactions 32S+58,64Ni are studied at 14.5 AMeV. From this energy on, fragmentation begins to be a dominant process, although evaporation and fission are still present. After a selection of the collision mechanism, we show that important even-odd effects are present in the isotopic fragment distributions when the excitation energy is small. The staggering effect appears to be a universal feature of fragment production, slightly enhanced when the emission source is neutron poor. A closer look at the behavior of isotopic chains reveals that odd-even effects cannot be explained by pairing effects in the nuclear mass alone, but depend in a more complex way on the de-excitation chain.